IOT-ENABLED SMART LIGHTING SYSTEM WITH INTEGRATED PULLEY MECHANISM FOR HOME AUTOMATION - Nazhatul Hafizah Kamarudin; Mohammad Arif Ilyas; Fadilla ‘Atyka Nor Rashid; Fazlina Mohd Ali (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Lighting systems play a fundamental role in our daily life operations. However, the typical light bulb has a finite lifespan and is often installed in hard-to-reach locations, posing a challenge when it needs replacement. To address this issue, we’ve developed an IoT bulb holder equipped with a pulley mechanism designed to lower itself to a user-accessible height. This innovative system also features built-in light control functionality. Our solution integrates a microcontroller with a Wi-Fi module, a mechanical motor for the pulley mechanism, and an Android app. The Android app serves as the central control hub for the system. The microcontroller manages the DC motor’s position and light control, responding to instructions from the app. Light control is achieved through a relay circuit, while the pulley mechanism is operated using a DC motor with a worm gearbox. The worm gearbox was chosen for its self-locking capabilities, eliminating the need for continuous power to maintain the light bulb at the desired height. 3D modeling software was utilized to create the casing and gearing components. Tests with two different microcontrollers: NodeMCU ESP8266 and ESP32 have been conducted. A comparative analysis revealed that the ESP32 is the superior choice for IoT projects due to its enhanced Wi-Fi efficiency and connectivity capabilities.